The Effect of Biogas Waste Doses (Sludge) of Cow Manure on the Growth and the Yield of Eggplant (Solanum Melongena L.) - Mas'udi, Ach Fauzan; Setyawan, Hidayat Bambang (Graduate School, Universitas Brawijaya, 2019)
The growth and the yield of eggplant plants are strongly influenced by the condition of the soil, and any damage to soil quality can cause unproductive plants according to its potential results. The addition of organic material in the form of biogas waste into the soil is expected to increase the yield of eggplant. This experiment aims at determining the best dose of biogas waste (sludge) to increase eggplant production. The experiment was carried out in Jember Lor village, Patrang, Jember, East Java with an altitude of Â± 89 meters above sea level (masl). The experiment used a completely randomized design method (CRD) with 4 treatments, treatment L0: 0kg waste plant-1; L1: 0.6 kg of waste. L2: 1,2kg of waste plants -1 and L3: 2,2 kg of waste plants-1. Each treatment was repeated 6 times with a total of 24 plants. Based on the results of the study, there was a very significant effect of sludge on variables of plant height, flowering age, harvesting age, fruit diameter, fruit length, and fruit weight. Sludge does not show a significant difference in plant diameter variables. The best treatment to have reached the plant height, fruiting age, harvesting age, fruit diameter, fruit length and fruit weight was the treatment of using a sludge with the dose of 1.2 kg polybag-1 (L2) with a height of 102.8 cm, different ages of 30.83 HST , harvest age of 56.73 HST, fruit diameter of 35.93 mm, fruit length of 17.95 cm and fruit weight of crop reached 1.36 kg (37.61 tons ha-1).Keywords: biogas waste, cow dung, eggplant, sludge.